Sengketa Hukum Penggunaan Non Navigasi Jalur Air Internasional Antar Negara Perbatasan - Lidia Wihelmina Tutuhatunewa; Veriena Josepha Batseba Rehatta (Faculty of Law, Universitas Pattimura, 2021)
Introduction: On 6 June 2016 Chile sued Bolivia for its claim that the Silala river belong to Bolivia in its entirety and is not an international watercourse. The problems studied are the regulation on the use of non-navigating international watercourses formulated by international legal instruments and the law of non-navigational uses of international watercourse between Bolivia-Chile as border countries.Purposes of the Research: The purpose of this research is to resolve the border dispute between Bolivia and Chile, to find a middle point or a better solution.Methods of the Research: This study uses a normative juridical method with the legal material used in the study is the Non-Navigational Law on the Use of International Watercourses (UNWC) with the use of literature study techniques in the form of international legal regulations, scientific works and literature.Results of the Research: The results of this study indicate that the regulation on the use of non-navigational international waterways is formulated in an international legal instrument, namely the United Nation Convention on the Law of the Non-navigational Uses of International Watercourses ( UNWC) and the bilateral agreement between Bolivia and Chile, namely the 1904 Treaty of Peace & Friendship (Peace Agreement 1904) and is used as a source of law to resolve the Silala River dispute case. Meanwhile, the settlement of legal disputes on the use of non-navigating international waterways between the Bolivia-Chile border countries can be resolved by means of mediation. Both parties can use the Convention on the Law on the Use of Non-Navigation of International Watercourse and the provisions agreed upon in the bilateral agreement, namely the Treaty of Peace & Friendship 1904 as the main legal material to reach an agreement. Or both parties can stick to their respective demands and defenses.